The radio structure of the narrow-line Seyfert 1 Mrk 783 with VLBA and e-MERLIN. Issue 3 (1st October 2020) - Congiu, E; Kharb, P; Tarchi, A; Berton, M; Caccianiga, A; Chen, S; Crepaldi, L; Di Mille, F; Järvelä, E; Jarvis, M E; La Mura, G; Vietri, A
ABSTRACT: In this paper, we present the analysis of new radio and optical observations of the narrow-line Seyfert 1 galaxy Mrk 783. $1.6\, GHz$ observations performed with the e-MERLIN interferometer confirm the presence of the diffuse emission previously observed. The Very Long Baseline Array (VLBA) also detects the nuclear source both at $1.6\, GHz$ ( L band) and $5\, GHz$ ( C band). While the L -band image shows only an unresolved core, the C -band image shows the presence of a partially resolved structure at a position angle of 60 ○ . The brightness temperature of the emission in both bands (${\gt}10^6\, K$ ) suggests that it is a pc-scale jet produced by the active galactic nucleus. The relatively steep VLBA spectral index (αVLBA = 0.63 ± 0.03) is consistent with the presence of optically thin emission on milliarcsecond scales. Finally, we investigated two possible scenarios that can result in the misalignment between the kpc and pc-scale radio structure detected in the galaxy. We also analysed the optical morphology of the galaxy, which suggests that Mrk 783 underwent a merging in relatively recent times.